Studies toward the synthesis of potent anti-inflammatory peptides solomonamides A and B: synthesis of a macrocyclic skeleton and key fragment 4-amino-6-(2 `-amino-4 `-hydroxyphenyl)-3-hydroxy-2-methyl-6-oxohexanoic acid (AHMOA) - Kashinath, K.; Vasudevan, N.; Reddy, D. Srinivasa (Organic Letters, 2012)
A first synthetic effort toward total synthesis of highly potent solomonamides is disclosed. An efficient strategy to synthesize this class of compounds, along with the synthesis of a core macrocycle (shown in red) and the key fragment AHMOA, is described.